The Regulation and Expression of the Creatine Transporter: A Brief Review of Creatine Supplementation in Humans and Animals - Schoch, Ryan D (BioMed Central, 2006)
Creatine monohydrate has become one of the most popular ergogenic sport supplements used today. It is a nonessential dietary compound that is both endogenously synthesized and naturally ingested through diet. Creatine ingested through supplementation has been observed to be absorbed into the muscle exclusively by means of a creatine transporter, CreaT1. The major rationale of creatine supplementation is to maximize the increase within the intracellular pool of total creatine (creatine + phosphocreatine). There is much evidence indicating that creatine supplementation can improve athletic performance and cellular bioenergetics, although variability does exist. It is hypothesized that this variability is due to the process that controls both the influx and efflux of creatine across the cell membrane, and is likely due to a decrease in activity of the creatine transporter from various compounding factors. Furthermore, additional data suggests that an individual's initial biological profile may partially determine the efficacy of a creatine supplementation protocol. This brief review will examine both animal and human research in relation to the regulation and expression of the creatine transporter (CreaT). The current literature is very preliminary in regards to examining how creatine supplementation affects CreaT expression while concomitantly following a resistance training regimen. In conclusion, it is prudent that future research begin to examine CreaT expression due to creatine supplementation in humans in much the same way as in animal models.